Chinese Stardom in Participatory Cyberculture - Lau, Dorothy Wai Sim (Edinburgh University Press, 2018)
As Chinese performers have become more visible on global screens, their professional images - once the preserve of studios and agents - have been increasingly relayed and reworked by film fans. Web technology has made searching, poaching, editing, posting and sharing texts significantly easier, and by using a variety of seamless and innovative methods a new mode of personality construction has been developed. With case studies of high-profile stars like Jet Li, Jackie Chan and Donnie Yen, this ground-breaking book examines transnational Chinese stardom as a Web-based phenomenon, and as an outcome of the participatory practices of cyber fans.